Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.21121/eab.2009319694
|View full text |Cite
|
Sign up to set email alerts
|

A Research on the Effect of Organizational Safety Climate Upon the Safe Behaviors

Abstract: This study aims to investigate the relationship between the organizational safety climate and the safety behaviors of the employees. It is been accepted by many researchers that unsafe employee behavior at work place is one of the primary determinants of occupational accidents. More recently researchers suggest that safe/unsafe behaviors of the employees are affected by certain organizational factors. Recent studies accept organizational safety climate as one these factors that affects safe/unsafe behaviors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…güvenlik ikliminin değerlendirildiği güvenlik performansı veya davranışları arasındaki ilişkileri inceleyen çalışmalar [9][10][11][12][13] olduğu gibi güvenlik iklimini etkileyen değişkenleri tespit etmek için yapılan çalışmalar da [14][15][16][17][18][19][20][21][22] mevcuttur. Karadurmuş (2006) tarafından yapılan çalışmada Avrupa Birliği'nin iş sağlığı ve güvenliği ile ilgili stratejisini önleme kültürünü güçlendirmek için eğitim ve öğretimi ön plana çıkardığını, İSG eğitiminin iş hayatına atılınca değil okul müfredatının bir parçası olması gerektiği vurgulanmaktadır.…”
Section: Literatürdeunclassified
“…güvenlik ikliminin değerlendirildiği güvenlik performansı veya davranışları arasındaki ilişkileri inceleyen çalışmalar [9][10][11][12][13] olduğu gibi güvenlik iklimini etkileyen değişkenleri tespit etmek için yapılan çalışmalar da [14][15][16][17][18][19][20][21][22] mevcuttur. Karadurmuş (2006) tarafından yapılan çalışmada Avrupa Birliği'nin iş sağlığı ve güvenliği ile ilgili stratejisini önleme kültürünü güçlendirmek için eğitim ve öğretimi ön plana çıkardığını, İSG eğitiminin iş hayatına atılınca değil okul müfredatının bir parçası olması gerektiği vurgulanmaktadır.…”
Section: Literatürdeunclassified
“…Occupational hazards could result from the nature of materials/equipment being used, environment under which work is being done as well as the people involved in specific activities. Sadullah and Kanten [22] also classified the causes of occupational hazards into unsafe work conditions and unsafe behaviors. The fisheries industry like other agricultural activities especially in the developing countries is one that involves people of different age categories such as children and adults.…”
Section: Overview Of Occupational Hazardsmentioning
confidence: 99%
“…Previous studies have found work pressure to have a significant influence on safety behavior as well as occupational accidents (e.g. Pordanjani & Ebrahimi, 2015;Sadullah & Kanten, 2009). For example, Bronkhorst (2015) conducted a study on 6230 health care employees of 52 organisations and found that work pressure has a significantly negative influence on physical safety behavior.…”
Section: Work Pressure and Safety Behaviourmentioning
confidence: 99%